2012
DOI: 10.1021/jz301890m
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing Infrared Photons for Photoelectrochemical Hydrogen Generation. A PbS Quantum Dot Based “Quasi-Artificial Leaf”

Abstract: Hydrogen generation by using quantum dot based heterostructures has emerged as a promising strategy to develop artificial photosynthesis devices. In the present study, we sensitize mesoporous TiO 2 electrodes with in-situ deposited PbS/CdS quantum dots (QDs), aiming at harvesting light in both the visible and the near infrared for hydrogen generation. This heterostructure exhibits a remarkable photocurrent of 6 mA·cm -2 leading to 60 ml·cm -2 ·day -1 hydrogen generation. Most importantly, confirmation of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 44 publications
1
78
1
Order By: Relevance
“…Typical sensitizers of nanocrystalline titania (nc-TiO 2 ) is CdS, CdSe, PbS, etc. [1][2][3][4][5]. Almost all of them are usually synthesized on nc-TiO 2 films by Chemical-Bath-based procedures, which are very successful but time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…Typical sensitizers of nanocrystalline titania (nc-TiO 2 ) is CdS, CdSe, PbS, etc. [1][2][3][4][5]. Almost all of them are usually synthesized on nc-TiO 2 films by Chemical-Bath-based procedures, which are very successful but time-consuming.…”
Section: Introductionmentioning
confidence: 99%
“…The visible light response decreases while the electron injection driving force increases as the decrease of the particle size [64,65]. PbS/CdS co-sensitized mesoporous TiO 2 further extends the absorption spectral range to infrared photons [66]. TiO 2 /PbS/ CdS heterostructures exhibit a photocurrent density of 6 mA cm À2 .…”
Section: Quantum Dot (Qd) Sensitizationmentioning
confidence: 98%
“…Recently, Trevisan et al demonstrated in situ growth of CdS and PbS QDs on mesoporous TiO 2 aiming at harvesting light in both visible and NIR regions and their application for PEC hydrogen generation. 101 In addition to in situ approaches, post-synthesis assembly approaches for QD sensitization have been also investigated. In particular, the simultaneous use of QDs with different, well-controlled sizes can be realized by the post-synthesis assembly.…”
Section: -7mentioning
confidence: 99%